Wykorzystanie koncepcji time based managements w procesie ewolucyjnego wdrażania organizacji lean - Nogalski, Bogdan; Walentynowicz, Piotr (The use of the concept of time-based management in the process of evolutionary implementation of lean management, 2006)
For years, there has been a constant interest in the concepts, which rationalize and economize the process of enterprise management. Among many methods allowing for a leaner enterprise, one should mention time-based management, as having a large potential for application. The purpose of this paper is to show the potential of time-based management, as an important element in building a strategy of competition and its evolutionary use in change management, against the background of streamlining and sliming of a company. This concept – after appropriate preparation - may constitute a valuable asset, which builds the competitive potential of the enterprise, and is instrumental to achieving competitive advantage.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 570-577